2021
DOI: 10.2147/ppa.s291983
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment in Patients with Rheumatoid Arthritis from Spain

Abstract: Objective: To evaluate adherence to treatment in a cohort of patients with rheumatoid arthritis in Spain and to identify potential predictors of adherence. Methods: An observational, cross-sectional, multicenter study in outpatient clinics of Rheumatology Departments from 41 centers was conducted. A validated Spanish version of the compliance questionnaire in Rheumatology was used to measure adherence in a cohort of patients with rheumatoid arthritis, representative of the Spanish population. Univariate and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Bak-Sosnowska et al concluded that elderly patients appeared to use pharmacotherapy more systematically, which may result from a greater level of adaptation to the disease and its acceptance compared to younger patients, but also from objective factors, such as regular daily routine or more free time [ 2 ]. On the other hand, through ANOVA analysis, age was not identified as a predictor of adherence in a cross-sectional, multi-center study performed in Spain which is consistent with results obtained by Alrubaye et al in Iraq [ 20 , 21 ].…”
Section: Reviewsupporting
confidence: 88%
See 2 more Smart Citations
“…Bak-Sosnowska et al concluded that elderly patients appeared to use pharmacotherapy more systematically, which may result from a greater level of adaptation to the disease and its acceptance compared to younger patients, but also from objective factors, such as regular daily routine or more free time [ 2 ]. On the other hand, through ANOVA analysis, age was not identified as a predictor of adherence in a cross-sectional, multi-center study performed in Spain which is consistent with results obtained by Alrubaye et al in Iraq [ 20 , 21 ].…”
Section: Reviewsupporting
confidence: 88%
“…The complexity of a patient’s drug regimen, which includes but is not limited to multiple medications, numerous doses, and specific time requirements, is related to poorer adherence to RA [ 19 , 20 ]. A review of literature studies was analyzed, which confirmed that the number of doses per day, as well as the complexity of the drug schedule, was inversely proportional to adherence [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the IV formulation, CT-P13 SC may afford patients more control over their treatment [ 125 ], with increased flexibility and convenience [ 13 ]. In turn, this could improve adherence: a Spanish observational study in RA concluded that compliance could be increased with less complex regimens [ 126 ]. HCPs must ensure that patients receive sufficient information and guidance to safely continue to self-administer SC therapeutics, including CT-P13 SC, over the long-term.…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…7 , 8 These situations are closely related in that healthy older adults and patients with RA both make substantial efforts in terms of drug-taking in their daily lives, including the use of personal devices to improve the ease of opening ( Table 5 ). 9 , 10 Patients with RA tend to have weak pinch power, so these issues could pose more serious problems. The fact that a high percentage of patients use their own devices also suggests the need for better drug-taking support.…”
Section: Discussionmentioning
confidence: 99%